Left-Wing SPA-Led and CPUSA-Led Unions and Worker Organizations as the Vanguard of U.S. Social Democracy's Left-Wing, Circa 1935 to 1950. (March 2019) - Devinatz, Victor G.
During the golden era of world trade unionism (circa 1945 to 1980) the trade union movement's political arm, the workers' parties (Labor, Social Democratic, and Communist) were at their peak strength attaining a significant amount of electoral support from the citizens in many European industrial democracies. This situation, however, did not occur in the United States where both the Socialist Party of America (SPA) and the Communist Party USA (CPUSA) never exerted similar political power as their European counterparts. Nevertheless, SPA and CPUSA members and their supporters attained significant influence in U.S. trade unions and related workers' organizations, circa 1930 to 1950. Based on the publication of recent literature, I argue that left-wing SPA-led and CPUSA-led unions and worker organizations were the vanguard of the left wing of U.S. social democracy (the New Deal) from the mid-1930s to approximately 1950. Since the SPA and CPUSA had relatively small membership numbers, it was more effective for these political groups to work through trade unions and other mass worker organizations, such as the International Workers Order, for promoting their ideas and policies.